Peran Guru dalam Implementasi Mobile Seamless Learning untuk Pembelajaran Membaca Awal Anak Usia Dini - Adiyati Fathu Roshonah; Anita Damayanti; Rita Mariyana; Putri Hayatunnisa (Journal on Education, 2024)
This study aims to analyze the role of teachers in the implementation of mobile seamless learning for early childhood reading learning. The use of technology as a learning medium for early childhood is a necessity in order to obtain benefits in the form of more optimal learning outcomes, but on the other hand, efforts are also needed to minimize the negative impact of the use of technology. This study uses a qualitative descriptive method to obtain a comprehensive picture of the role of teachers in the application of mobile seamless learning for early childhood reading learning in early childhood learning in early childhood education institutions. The research participants were 25 PAUD/TK teachers in the Greater Jakarta area, aged 23-54 years and had been PAUD/TK teachers for 2-14 years. The results of the study showed that all participants stated the importance of mobile seamless learning in early childhood reading learning. The implementation of mobile seamless learning has been implemented in PAUD Institutions even though it has not been implemented consistently due to various factors such as limited data packages, signals that are not always good and limitations of supporting devices (infocus). The applications used include Canva, Youtube, Let's Read Digital Books, Paud Pedia, Arloopa and Quiver. All participants expressed the high enthusiasm of students when teachers implemented mobile seamless learning. The role of teachers in the implementation of mobile seamless learning for early childhood reading learning includes as teachers, directors, learning resources, facilitators, managers, role models (role models), supervisors, motivators and evaluators. The results of this study also show the urgency of providing a system that includes facilities and infrastructure to support the implementation of mobile seamless learning which needs to be accompanied by an increase in the digital competence of PAUD teachers related to the effectiveness of the use of digital media in the learning process.